Immune Cell Activation in the Cerebrospinal Fluid of Patients With Parkinson's Disease - Schröder, Jens B.; Pawlowski, Matthias; Meyer zu Hörste, Gerd; Gross, Catharina C.; Wiendl, Heinz; Meuth, Sven G.; Ruck, Tobias; Warnecke, Tobias (Frontiers in Neurology, 2018)
Background: Parkinson's disease (PD) is a common neurodegenerative disorder. The contribution of the immune system to its pathogenesis remains incompletely understood. Methods: In this study, we performed comprehensive immune cell profiling in the cerebrospinal fluid (CSF) and peripheral blood (PB) of PD patients. Ten PD patients were diagnosed according to brain bank criteria and underwent detailed clinical examination, magnetic resonance imaging, PB and CSF immune cell profiling by multiparameter flow cytometry, and cytokine and chemokine measurements by bead-based arrays. Thirteen healthy elderly volunteers served as control population. Results: The proportions of activated T-lymphocytes and non-classical monocytes in the CSF were increased in patients with PD compared to the control group. In accordance, we found increased levels of the pro-inflammatory cytokines IL-2, IL-6 and TNFα and of the monocyte chemoattractant protein 1 (MCP-1) in the CSF of the included PD patients. Conclusions: Our data provide novel evidence for a response of the innate and adaptive immune system in the central nervous system of patients with PD.